(untitled) (Transport systems and technologies, 2019)
Based on the objective need for the development of cargo transportation under mixed schemes, in particular, container transportation, there is the task of creating a fleet of specialized cars. At the same time, it should be emphasized the importance of increasing the speed of trains of combined transport provided guaranteed operational safety. In this way, the new generation of cars, according to their dynamic characteristics, should provide resistance to climbing rails throughout the given range of speeds. The article deals with the issues of maintenance of technical operation of platform cars for high-speed container transportations by means of application of running gears of a new type. Due to the fundamental shortcomings of wagon-wide trucks, the possibility of using the equipment for high-speed platform cars with axle box spring suspension was considered. Proceeding from the high efficiency of the application of mathematical modeling to determine the indicators of the dynamics of the movement of rail vehicles, to assess the conditions for ensuring the safety of the movement of platform cars, appropriate computer models were built. According to the simulation results, it was found that under the conditions of stability of wheel pairs from derailment the condition of safe operation of a platform car on trucks with axle box spring suspension is met at speeds up to 150 km/h inclusive, while the safety of the movement of a platform car with standard type trucks is provided at speeds up to 100 km/h. This conclusion gives grounds for a recommendation on the equipment of platform cars for high-speed combined transport by running gear with an axle box spring suspension.